Teori Belajar Behavioristik Edward Lee Thorndike dan Penerapannya dalam Pembelajaran Pendidikan Agama Katolik - Paulinus Kanisius Ndoa; Sitepanus Zebua; Anna Silfan Gulo (Jurnal Magistra, 2025)
This paper aims to examine in depth the application of the behaviorist learning theory proposed by Edward Lee Thorndike in the learning process of Catholic Religious Education. Thorndike emphasized that the learning process occurs through the relationship between stimuli and responses, which are strengthened through repeated practice and reinforcement. This reinforcement can be in the form of awards such as praise and prizes, or punishments that function to strengthen or weaken certain responses. In this study, the author also describes in detail the basic laws in Thorndike's theory which are the foundation for implementing the behaviorist approach in teaching and learning activities. Furthermore, this theory can be applied practically in Catholic Religious Education learning by providing appropriate stimulus and reinforcement to students through directed learning activities. The stimulus and reinforcement have the potential to encourage changes in attitudes and behavior in a more positive direction, in accordance with the values ​​of the Catholic faith. Therefore, teachers as learning facilitators need to develop learning strategies that are planned, structured, and able to shape students' character and faith comprehensively and continuously.